Increased loading, efficacy and sustained release of silibinin, a poorly soluble drug using hydrophobically-modified chitosan nanoparticles for enhanced delivery of anticancer drug delivery systems - Cha, Yee Kuen; Fakurazi, Sharida; Othman, Siti Sarah; Masarudin, Mas Jaffri (MDPI, 2017)
Conventional delivery of anticancer drugs is less effective due to pharmacological drawbacks such as lack of aqueous solubility and poor cellular accumulation. This study reports the increased drug loading, therapeutic delivery, and cellular accumulation of silibinin (SLB), a poorly water-soluble phenolic compound using a hydrophobically-modified chitosan nanoparticle (pCNP) system. In this study, chitosan nanoparticles were hydrophobically-modified to confer a palmitoyl group as confirmed by 2,4,6-Trinitrobenzenesulfonic acid (TNBS) assay. Physicochemical features of the nanoparticles were studied using the TNBS assay, and Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) analyses. The FTIR profile and electron microscopy correlated the successful formation of pCNP and pCNP-SLB as nano-sized particles, while Dynamic Light Scattering (DLS) and Field Emission-Scanning Electron Microscopy (FESEM) results exhibited an expansion in size between pCNP and pCNP-SLB to accommodate the drug within its particle core. To evaluate the cytotoxicity of the nanoparticles, a Methylthiazolyldiphenyl-tetrazolium bromide (MTT) cytotoxicity assay was subsequently performed using the A549 lung cancer cell line. Cytotoxicity assays exhibited an enhanced efficacy of SLB when delivered by CNP and pCNP. Interestingly, controlled release delivery of SLB was achieved using the pCNP-SLB system, conferring higher cytotoxic effects and lower IC50 values in 72-h treatments compared to CNP-SLB, which was attributed to the hydrophobic modification of the CNP system.